The sharp rejoinder and the linguistic repartee: a linguistic experimental study in the structure rules - Alzabin, Emad Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study determines the laws of linguistic structures that cause linguistic shock in sharp rejoinders in an argumentative dialogue. Particularly, this research examines and analyses numerous sharp rejoinders, demonstrates the related laws, divides them into a set of linguistic matrices and explains the systems that cause the sharp rejoinders to assume that understanding these answers will raise the linguistic repartee level in our argumentative conversations. This experimental study used an experimental linguistic approach to explain the laws of these matrices to several students, specifically to show their effects when the linguistic repartee level is raised. Therefore, the current research is bifacial theoretical and experimental in nature. The experimental part showed the students’ ability to promptly produce the appropriate responses according to the experimental conditions. Consequently, the importance of studying the rules of linguistic structure was reflected when the linguistic repartee level of recipients is raised.